(untitled) (IJM: Journal of Multidisiplinary, 2025)
Oil palm is one of Indonesia’s main plantation commodities, whose productivity is strongly influenced by soil nutrient availability. Fertilization processes that do not consider soil conditions may lead to inappropriate fertilizer application. This study aims to design and test a prototype of an automatic oil palm fertilization system based on sensors and a microcontroller. The research method employed is Research and Development (R&D), which includes literature review, system design, hardware assembly, microcontroller programming, and system performance testing. The system utilizes a soil moisture sensor as the basis for fertilization and irrigation control, and an ultrasonic sensor for obstacle detection. The test results indicate that all system components operate with stable voltage values and comply with their technical specifications. The obstacle detection system is able to detect objects up to a distance of 100 cm and provides appropriate responses to the movement of the device. In addition, the automatic fertilization and irrigation system operates based on soil moisture conditions, where actions are performed when the soil is classified as dry. These results demonstrate that the developed prototype is capable of performing automatic oil palm fertilization in accordance with environmental conditions.